Investigating the Association of Wallerian Degeneration and Diaschisis After Ischemic Stroke With BOLD Cerebrovascular Reactivity - van Niftrik, C. H. B.; Sebök, M.; Muscas, G.; Wegener, S.; Luft, A. R.; Stippich, C.; Regli, L.; Fierstra, J. (Frontiers in Physiology, 2021)
Introduction: Wallerian degeneration and diaschisis are considered separate remote entities following ischemic stroke. They may, however, share common neurophysiological denominators, since they are both related to disruption of fiber tracts and brain atrophy over time. Therefore, with advanced multimodal neuroimaging, we investigate Wallerian degeneration and its association with diaschisis. Methods: In order to determine different characteristics of Wallerian degeneration, we conducted examinations on seventeen patients with chronic unilateral ischemic stroke and persisting large vessel occlusion, conducting high-resolution anatomical MRI and blood oxygenation-level dependent cerebrovascular reactivity (BOLD-CVR) tests, as well as Diamox 15(O)-H2O-PET hemodynamic examinations. Wallerian degeneration was determined using a cerebral peduncle asymmetry index (% difference of volume of ipsilateral and contralateral cerebral peduncle) of more than two standard deviations away from the average of age-matched, healthy subjects (Here a cerebral peduncle asymmetry index > 11%). Diaschisis was derived from BOLD-CVR to assess the presence of ipsilateral thalamus diaschisis and/or crossed cerebellar diaschisis. Results: Wallerian degeneration, found in 8 (47%) subjects, had a strong association with ipsilateral thalamic volume reduction (r2=0.60) and corticospinal-tract involvement of stroke (p<0.001). It was also associated with ipsilateral thalamic diaschisis (p=0.021), No cerebral peduncular hemodynamic differences were found in patients with Wallerian degeneration. In particular, no CBF decrease or BOLD-CVR impairment was found. Conclusions: We show a strong association between Wallerian degeneration and ipsilateral thalamic diaschisis, indicating a structural pathophysiological relationship.